2009
DOI: 10.1093/bja/aep201
|View full text |Cite
|
Sign up to set email alerts
|

Profound haemodilution during normothermic cardiopulmonary bypass influences neither gastrointestinal permeability nor cytokine release in coronary artery bypass graft surgery

Abstract: Profound haemodilution during normothermic CPB brought about significant changes neither in intestinal permeability nor in cytokine release. It may be concluded that a haematocrit of 19-21% during normothermic CPB does not impair intestinal barrier function and cytokine response in patients without gastrointestinal comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
1
4
0
1
Order By: Relevance
“…Whereas the effect of CPB on clearance was quite obvious, we did not observe an effect of CPB initiation on volume of distribution, although the priming of the bypass circuit with crystalloids causes haemodilution, 22 which was also indicated by the decrease in haematocrit in the present study (Table 2). However, changes in the central volume of distribution have been shown to balance out quickly by redistribution of sufentanil from peripheral compartments.…”
Section: Discussionsupporting
confidence: 40%
“…Whereas the effect of CPB on clearance was quite obvious, we did not observe an effect of CPB initiation on volume of distribution, although the priming of the bypass circuit with crystalloids causes haemodilution, 22 which was also indicated by the decrease in haematocrit in the present study (Table 2). However, changes in the central volume of distribution have been shown to balance out quickly by redistribution of sufentanil from peripheral compartments.…”
Section: Discussionsupporting
confidence: 40%
“…Moreover, the cytokine interleukin-6 (IL-6) can influence the HPA axis directly by stimulating the glucocorticoid release on the adrenal glands [43,44]. The release of IL-6 usually starts within 60 min after surgical procedures [45,46] and positively correlates with the corticosterone concentration [43,47]. In conclusion, the long-lasting corticosterone response after surgery might arise from the summation of distress parameters that influence the HPA axis.…”
Section: Discussionmentioning
confidence: 99%
“…Transfusion triggers for the study groups were determined from information obtained from previous studies that showed that hematocrit values as low as 22% are safe in cardiac surgery with cardiopulmonary bypass. 14,15 Patients assigned to the liberal-strategy group received RBC transfusions if the hematocrit was less than 30% at any time from the start of surgery until discharge from the ICU. Patients assigned to the restrictivestrategy group received RBC transfusions if hematocrit values were less than 24%.…”
Section: Study Design and Treatment Strategiesmentioning
confidence: 99%